2017
DOI: 10.1073/pnas.1616769114
|View full text |Cite
|
Sign up to set email alerts
|

Architected cellular ceramics with tailored stiffness via direct foam writing

Abstract: Hierarchical cellular structures are ubiquitous in nature because of their low-density, high-specific properties, and multifunctionality. Inspired by these systems, we created lightweight ceramic architectures composed of closed-cell porous struts patterned in the form of hexagonal and triangular honeycombs by direct foam writing. The foam ink contains bubbles stabilized by attractive colloidal particles suspended in an aqueous solution. The printed and sintered ceramic foam honeycombs possess low relative den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
140
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(143 citation statements)
references
References 46 publications
2
140
0
Order By: Relevance
“…Digital photographs of honeycombs are illustrated in Figure 7A,B, showing that the honeycombs with various sizes and shapes can be obtained. 18 The crosses of the filaments manifested nearly seamless integration of printed filaments with porous microstructure (Figure 7D,E). Phase compositions of specimens determined by XRD indicated that magnesium aluminate spinel (MgAl 2 O 4 ) was the only crystalline phase as a consequence of chemical reaction between Al 2 O 3 and MgO.…”
Section: Phase Composition and Microstructurementioning
confidence: 95%
See 2 more Smart Citations
“…Digital photographs of honeycombs are illustrated in Figure 7A,B, showing that the honeycombs with various sizes and shapes can be obtained. 18 The crosses of the filaments manifested nearly seamless integration of printed filaments with porous microstructure (Figure 7D,E). Phase compositions of specimens determined by XRD indicated that magnesium aluminate spinel (MgAl 2 O 4 ) was the only crystalline phase as a consequence of chemical reaction between Al 2 O 3 and MgO.…”
Section: Phase Composition and Microstructurementioning
confidence: 95%
“…Among these methods, direct ink writing (DIW) is an attractive and versatile 3D printing technology to construct multifunctional structures for the applications in various fields ranging from smart composites, 6,7 bioinspired materials, 8,9 and electron component. 17,18 This method was defined as "direct foam writing" (DFW). The inks usually possess similar rheological properties, that is, shear thinning and viscoelasticity, 12,13 to assistant the printing process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrent usage of AM with other methods (eg, emulsified wet foam 3D printing) provides design freedom so that not just sophisticated shapes (microarchitected truss structures) and precise control of the pore character becomes possible but also less defected structures and consequently enhanced strength is attainable. However, currently there are still problems such as low density and resolution, poor surface finish, flaws, and most importantly very high cost (of one‐pot printing devices) for small lot manufacturing.Wet foams synthesized by Muth et al were used to obtain predefined, bio‐inspired hierarchical architectures with mixed mode mechanical responses; in Figure A‐C, anode with multiple strut connectivity and inner microstructure is given. The manufactured components had bending‐dominated hexagonal or stretching‐dominated triangular trusses constituted by closed porosity (or nearly dense) imposing additional bending‐dominated response by altering the processing parameters (ink composition, geometry, dry and sintering).…”
mentioning
confidence: 99%
“…(A) Printed and sintered component with triangular cells, and (B) the close magnification image of a node, and (C) the resulting SEM image showing the closed porosity microstructure of the node (Reproduced with permission from)…”
mentioning
confidence: 99%